Promoting a culture change in junior and youth sport in New Zealand - Walters, Simon R.; Minjares, Vincent; Bradbury, Trish; Lucas, Patricia; Lenton, Andrew; Spencer, Kirsten; Spencer, Simone (Frontiers in Sports and Active Living, 2022)
This paper provides insight into the evolution of a project designed to address longstanding adult attitudes and behavioural issues in junior and youth sport in New Zealand. The project was funded by Sport New Zealand (Sport NZ) and implemented by Aktive, a charitable trust that works with national and regional partners to fund and deliver community sport in Auckland. Aktive collaborated with a team of junior and youth sport researchers, adopting a pragmatic, mixed methods design-based research (DBR) approach to co-design an educational delivery framework aimed at influencing attitudes and assumptions underpinning coaches, parents, and community sport leaders' behaviours. Transformative learning principles informed the delivery framework with the project reaching 4,222 participants. Research evaluations included multiple case studies, surveys, semi-structured interviews, and focus groups, which confirmed awareness of problematic beliefs. The programme expanded to Regional Sport Organisations (RSOs) and National Sport Organisations (NSOs) culminating in a nationwide rollout. The study highlights the effectiveness of theoretically informed adult behaviour change programmes in junior and youth sport, the benefits of programmes being underpinned by a rigorous pedagogical approach, and the benefits of sport organisations and researchers collaborating to design and deliver sustainable change initiatives that address belief systems underpinning current issues.